Prevalence of work-related musculoskeletal disorder and ergonomic risk practice among medical laboratory professionals at health facilities of eastern Ethiopia - Fikre, Dagim; Hawulte Ayele, Behailu; Sime, Akewok; Tebeje, Fikru; Weldegebreal, Fitsum (Frontiers in Public Health, 2024)
BackgroundMusculoskeletal disorders represent a significant occupational problem due to poor ergonomic workstations among medical laboratory professionals; however, there is limited information regarding ergonomic-related musculoskeletal disorders among laboratory personnel in Ethiopia, particularly in eastern Ethiopia.MethodsAn institutional-based cross-sectional study design was implemented among 241 Medical Laboratory Professionals (MLPs) from December 20, 2023, to January 20, 2024. A standardized questionnaire adapted from the Nordic musculoskeletal questionnaire and a combination of self-administered surveys and direct observational techniques was used for data collection. Bivariate and multivariable logistic regression analyses were used to determine factors associated with musculoskeletal disorders with findings presented through Odds ratios and a 95% Confidence Interval (CI), and statistical significance was declared at p-value <0.05.ResultThis study showed that over the past 12 months, 142 (58.9%; 95% CI: 52.0, 65.0) Medical Laboratory professionals reported work-related musculoskeletal disorders at least in one of the nine body parts. Age 36 and above years (AOR = 1.51; 95% CI: 1.02, 6.01), being female (AOR = 1.89; 95% CI: 1.09, 5.04), work experience 10–15 years (AOR = 3.99; 95% CI: 1.6, 9.4), work experience >15 years (AOR = 4.13; 95% CI: 1.52, 10.81), sitting time 4 and above hours (AOR = 2.25; 95% CI: 1.10, 4.63), patient load >300 (AOR = 2.67; 95% CI: 1.12, 7.46), and being overweight (AOR = 1.67; 95% CI: 1.04, 6.03) were factors significantly associated.ConclusionThe prevalence of work-related musculoskeletal disorders was found to be higher among Medical Laboratory Professionals as compared to previous research conducted in Ethiopia. It is recommended to regularly evaluate workstations to reduce strain through adjustments in the chair and bench heights and implement task rotation to reduce repetitive movements and distribute physical demands among staff, in addition to that, adjust work schedules to include intermittent breaks. Tailored ergonomic solutions and flexible arrangements should be provided for female professionals who are at a higher risk for work-related musculoskeletal disorders. Furthermore, conducting routine health screenings to detect early signs of musculoskeletal disorders for timely intervention, as well as enhancing awareness among Medical Laboratory Professionals, are essential measures to mitigate ergonomic risk practice.